2023
DOI: 10.1101/2023.08.15.23294108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Benzodiazepine Exposure on Real-World Clinical Outcomes in Individuals at Clinical High-Risk for Psychosis

Nicholas R. Livingston,
Andrea De Micheli,
Robert McCutcheon
et al.

Abstract: Background: Animal models indicate GABAergic dysfunction in the development of psychosis, and that benzodiazepine (BDZ) exposure can prevent the emergence of psychosis-relevant phenotypes. However, whether BDZ exposure influences the risk of psychosis in humans is unknown. Methods: This observational-cohort study used electronic health record data from 818 individuals at clinical high-risk for psychosis (CHR-P) to investigate whether BDZ exposure (including hypnotics e.g., zopiclone) reduces the risk of develo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…To the Editors, Raballo, Poletti, and Preti (2023) recently published in this journal results of a meta-analysis investigating the association of baseline benzodiazepine (BDZ) exposure and risk of subsequent psychosis development in individuals at clinical high-risk for psychosis (CHR-P). As the authors state, this is an important, yet under-researched area given that prescription of BDZ to CHR-P individuals when joining a CHR-P service is relatively common (∼16-17%; Livingston et al 2023;Raballo et al 2023). With a small sample of only five studies included in the meta-analysis, the authors report that CHR-P individuals exposed to BDZs at baseline had an almost 2.5× increased risk of developing psychosis during the follow-up period (range 12-36 months) compared to those who were BDZ-unexposed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editors, Raballo, Poletti, and Preti (2023) recently published in this journal results of a meta-analysis investigating the association of baseline benzodiazepine (BDZ) exposure and risk of subsequent psychosis development in individuals at clinical high-risk for psychosis (CHR-P). As the authors state, this is an important, yet under-researched area given that prescription of BDZ to CHR-P individuals when joining a CHR-P service is relatively common (∼16-17%; Livingston et al 2023;Raballo et al 2023). With a small sample of only five studies included in the meta-analysis, the authors report that CHR-P individuals exposed to BDZs at baseline had an almost 2.5× increased risk of developing psychosis during the follow-up period (range 12-36 months) compared to those who were BDZ-unexposed.…”
mentioning
confidence: 99%
“…Therefore, the true association of BDZ exposure and subsequent psychosis transition is confounded. Our recent study (Livingston et al, 2023) was designed to examine the effects of baseline BDZ exposure (total number of days of BDZ exposure within ±3 months after accessing a CHR-P clinical service) on real-world clinical outcomes (occurring from 3 months after baseline until date of last observation) in 567 CHR-P individuals. In line with our observations above, we found that compared to individuals who were BDZ-unexposed (n = 462), those who were BDZ-exposed (n = 105) were more likely to be older, of Black ethnicity, have higher attenuated psychotic symptom (APS) severity, have shorter duration of untreated APS, and to have experienced a transient psychotic episode (brief limited intermittent psychotic symptoms, BLIPS).…”
mentioning
confidence: 99%